Electro-deposition Method for Platinum Nano-particles Synthesis - Islam, Md. Aminul; Islam, M. Saidul (Engineering International, 2013)
This review explores the recent development in the synthesis process of platinum nanoparticles by electro deposition method. Various developed supporting electrodes used in synthesis process of platinum nanoparticles have been discussed. It is possible to control the particle size by adjusting electrolysis parameters and to improve homogeneity of platinum particles by changing the composition of electrolytic solutions. Various electrolytic compositions also discuss briefly for single or mixed electrodes.